Penilaian Sikap Sopan Santun Peserta Didik Melalui Pembiasaan Lima Kata Ajaib di SD Negeri 106 Kota Bengkulu - Ramadhani, Restilia Ayu; Enike, Ririn; Lestari, Sindi; Siska; Agustian, Tegar Adri (Yayasan Darussalam Bengkulu, 2024)
This study aims to assess the politeness of students at SD Negeri 106 Bengkulu City through the habit of using five magic words, namely please, sorry, thank you, excuse me, and request permission. The research method uses a qualitative descriptive approach with observation and interview techniques. The research subjects include class teachers, students, and the results of daily attitude assessments. The results show that the habit of the five magic words consistently can increase students' awareness of the importance of being polite in communicating and interacting, both with teachers and fellow friends as well as habituation in daily life where students become more accustomed to using polite words in various situations at school, such as asking for help, expressing opinions, creating an atmosphere of mutual assistance or asking permission. In addition, the role of teachers as role models and reinforcement through attitude assessments also strengthen the formation of these positive behaviors. The conclusion of this study is that the habit of the five magic words is effective as a character learning strategy in improving the politeness of students in elementary schools.